2021
DOI: 10.1111/1756-185x.14223
|View full text |Cite
|
Sign up to set email alerts
|

Pain neuroscience education combined with usual treatment for fibromyalgia syndrome: A randomized controlled trial

Abstract: Fibromyalgia syndrome (FMS) is an important chronic condition seen in 2% to 5% of the general population, characterized by widespread pain and often accompanied by fatigue, cognitive problems, and sleep disturbances. 1 Although the etiology of FMS remains unclear, nociplastic pain has been reported as the most accepted mechanism in the pathophysiology of widespread pain experience and other symptoms related to FMS. 2,3 Different biologic factors may cause hyperexcitability of the central nervous system in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…19,22 The follow-up timings of the 9 studies completed in Turkey ranged from 6 weeks 23,24 to 6 months. 25 This compared with a range of 4 weeks to 12 months in the studies completed outside of Turkey. 22,26 All studies were conducted within a quantitative research paradigm, including nine randomised controlled trials (RCT's).…”
Section: Search Strategy and Selection Processmentioning
confidence: 99%
“…19,22 The follow-up timings of the 9 studies completed in Turkey ranged from 6 weeks 23,24 to 6 months. 25 This compared with a range of 4 weeks to 12 months in the studies completed outside of Turkey. 22,26 All studies were conducted within a quantitative research paradigm, including nine randomised controlled trials (RCT's).…”
Section: Search Strategy and Selection Processmentioning
confidence: 99%
“…The management of FM is currently divided between pharmacological and non‐pharmacological therapies. Patients often use a variety of strategies to manage their pain and comorbidities 5,6 . There are three drugs currently approved by the US Food and Drug Administration (FDA) for the treatment of FM, which are pregabalin, duloxetine, and milnacipran.…”
Section: Drug Mechanism Dosage Efficacy Tolerabilitymentioning
confidence: 99%
“…Patients often use a variety of strategies to manage their pain and comorbidities. 5,6 There are three drugs currently approved by the US Food and Drug Administration (FDA) for the treatment of FM, which are pregabalin, duloxetine, and milnacipran. Amitriptyline is a tricyclic antidepressant that is widely used off-label for the treatment of FM; 7 some studies even suggest that low doses of amitriptyline are the first choice for the treatment of FM.…”
mentioning
confidence: 99%
“…One of the recent adjuvant treatment options in a multimodal approach for FM is pain neuroscience education (PNE). 9 PNE, a kind of cognitive therapy aims to deeply understand and reconceptualize pain, thereby changing patients' previous beliefs and attitudes about pain. 10 Systematic reviews and meta-analyses addressing the effectiveness of PNE as in patients with chronic pain, concluded that PNE as an adjuvant therapy is an effective strategy on decreasing pain, catastrophizing, disability and improving beliefs and attitudes about pain.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent adjuvant treatment options in a multimodal approach for FM is pain neuroscience education (PNE) 9 . PNE, a kind of cognitive therapy aims to deeply understand and reconceptualize pain, thereby changing patients' previous beliefs and attitudes about pain 10 .…”
Section: Introductionmentioning
confidence: 99%